2017
DOI: 10.1371/journal.pone.0169049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Characterisation of Ireland's Green Tides (Ulva Species)

Abstract: Enrichment of nutrients and metals in seawater associated with anthropogenic activities can threaten aquatic ecosystems. Consequently, nutrient and metal concentrations are parameters used to define water quality. The European Union’s Water Framework Directive (WFD) goes further than a contaminant-based approach and utilises indices to assess the Ecological Status (ES) of transitional water bodies (e.g. estuaries and lagoons). One assessment is based upon the abundance of opportunistic Ulva species, as an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 68 publications
1
28
2
2
Order By: Relevance
“…However, the amount of Mn in the Irish Ulva species was related to the ecological quality index presented by the authors, whereas in the Swedish samples, in places of high fertilizer use, Mn was also observed in high concentrations. From both Ireland and the study presented here, no clear link between geographic location, anthropogenic input and metal content was found in the macroalgal species (Wan et al, 2017). Rather, it is the presence of elevated levels of macronutrients such as phosphorus in the water that enhance metal accumulation (Lee & Wang, 2001), as well as elevated runoff from the land that can lead to extensive deposition of metals in the sediments where the macroalgae are growing (Malea & Kevrekidis, 2014).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, the amount of Mn in the Irish Ulva species was related to the ecological quality index presented by the authors, whereas in the Swedish samples, in places of high fertilizer use, Mn was also observed in high concentrations. From both Ireland and the study presented here, no clear link between geographic location, anthropogenic input and metal content was found in the macroalgal species (Wan et al, 2017). Rather, it is the presence of elevated levels of macronutrients such as phosphorus in the water that enhance metal accumulation (Lee & Wang, 2001), as well as elevated runoff from the land that can lead to extensive deposition of metals in the sediments where the macroalgae are growing (Malea & Kevrekidis, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…An assessment of the variation of Ulva species in Ireland also examined a range of metal content across different species (such as Ulva compressa and U. intestinalis) over various sites having differing Ecological Status (Wan et al, 2017). Over all the sites examined in the study, the potentially toxic metal Cr was demonstrated to be at a magnitude lower than found across all the Swedish sites presented here.…”
Section: Discussionmentioning
confidence: 89%
“…Studies of sites with extensive blooms of Ulva intestinalis , U. compressa and U. lactuca revealed a decrease in the density of invertebrate populations (Bolam and Fernandes 2002 ). The green tides of Ulva substantially reduce the occurrence of the bottom fauna, thus diminishing the food base available to the marine macrofauna (Wan et al 2017 ). Likewise, plants and animals in inland waters are seldom encountered in the areas dominated by populations of U. flexuosa .…”
Section: Discussionmentioning
confidence: 99%
“…Considerable volumes of Ulva biomass are more than likely to affect the assets of the littoral areas in terms of tourist appeal (Charlier et al 2008 ). The deposition of rotten thalli on the beaches should be immediately taken care of, considering the ensuing release of hydrogen sulphide, carbon disulphide and methyl sulphide (Wan et al 2017 ). Mechanical or manual collection of Ulva biomass from the beaches as well as its management are very expensive (Gravier et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, any recommended/legislative safe limits for toxic elements in seaweeds, animal feeds or food products are likely to vary between countries and institutions (Wan et al . ). Many of these safe limits only focus on what is considered as ‘typical’ pollutants: arsenic, mercury, cadmium, chromium, lead and tin.…”
Section: Legislation and Safetymentioning
confidence: 97%